Cost-Volume-Profit Analysis for Profit Planning and Control in Hospitality Industry: A Study of Aloft, Kathmandu, Thamel - Shakya, Jeewan (MVIC Journal of Management and Information Technology, 2025)
This research examines the application of Cost-Volume-Profit (CVP) analysis in profit planning and control within the hospitality industry, with a focus on Aloft Kathmandu Thamel, a five-star hotel in Nepal. The study aims to evaluate how CVP analysis can enhance financial performance, especially in managing complex cost structures and fluctuating demand. Using secondary data from the hotel’s financial reports from 2019 to 2023, the research assesses the efficiency and cost-effectiveness of CVP as a tool for decision-making. The study finds that in 2019/20, the hotel’s sales performance was significantly below expectations, primarily due to external factors like the pandemic, but showed recovery in subsequent years. By 2022/23, the hotel surpassed its budgeted sales, indicating improved financial management. The contribution margin increased, and the break-even point (BEP) decreased over the study period, reflecting better cost control and operational efficiency. Statistical analysis reveals a strong correlation between budgeted and actual sales, highlighting accurate sales forecasting. The study concludes that Aloft Kathmandu Thamel’s use of CVP analysis has played a key role in its financial recovery and stability, suggesting that continuous cost management and monitoring are essential for long-term profitability in the hospitality industry.